COLLISION BINDINGS IN THE REGULATION OF LABOR RELATIONS WITH A FOREIGN ELEMENT - Александров, Олексій Володимирович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Aim: to identify some conflict problems in solving the choice of the right of the state when considering the labor conflict of laws with the participation of a foreign element and find ways to solve them. Methods of research: analysis, studying and comparising of international law, norms of civil law, which are used to regulate labor relations with a «foreign element». Results: a comprehensive study of the collisional legal regulation of labor relations with a foreign element was carried out, ways of solving the conflict problems between the national legal systems of different countries in the choice of the right of the country by the parties to the employment contract were determined, the regulation of the application of collision bindings with a foreign element was clarified. It is ascertained that in relation to labor relations complicated by a foreign element various conflicting principles are used. If the choice of the parties to the applicable law is not defined, then for the regulation of labor relations of an international nature,we use another collision bonds provided by the legal system of the country. First of all, this is the law of the place of work - lex loci laboris, which is enshrined in the laws of most countries. It is also traceable that the law of autonomy of the will of the parties - lex voluntatis, the law of the «closest connection» – has received the normative attachment in the sources of private international law. Discussion: to overcome the conflicts that arise in international private law. A labor contract with the participation of a foreign element is essential for overcoming the difficulties of the parties to the employment contract in case of a labor conflict in the choice of the country’s right. Bilateral agreements are the largest part of the international treaty base of Ukraine for labor contracts. Thus, to overcome the conflict problems arising in international private law as a result of the possibility of applying to one legal relationship in the extreme case of two legal systems, one can use two methods - conflict and substantive. Both methods complement each other and actively interact with each other. Formation of the legal basis for the protection of the interests of migrant workers is one of the necessary measures to implement their rights in practice. The principle (lex loci laboris) is increasingly reflected in the legislative activity of the countries every year, which is one of the prerequisites for preventing discriminatory treatment of workers employed by one employer.